Numerical Simulation Study on Directional Solidification of DD5 Nickel-Based Single-Crystal Turbine Blades - Jianhui Wei; Min Lu; Libo Pi; Huan Zhao; Qian Lei (Crystals)
Two models with a wax module tree structure were employed for directional solidification simulation. An experimental alloy of a second-generation nickel-based single-crystal superalloy, DD5, was set for this investigation. The temperature gradient value of the conventional model at 80 mm and 160 mm was less than 3.8 K/mm, and the temperature gradient value of the new model structure at the same height could reach more than 5.0 K/mm. The paste–liquid interface paste zone of the new model structure in the directional solidification process was narrower. The solidification interface was more stable than that of the conventional model. The declination angle between the primary dendrite and the principal stress axis was smaller, and the average crystal orientation was about 6.0°. Under the new model, the integrity of the single crystal of the edge plate was good, and no heterocrystalline defects were formed. At the sharp corner of the end face of the edge plate, the solidified dendrites grew staggered, which hindered the effective contraction of other parts of the edge plate and produced micro-looseness. The whole simulation was in line with the test results.